MANFAAT PIJAT OKSITOSIN UNTUK PENCEGAHAN PERDARAHAN IBU PASCA MELAHIRKAN - Elisa Elisa; Kurniati Puji Lestari; Iis Sriningsih (Jurnal LINK, 2016)
This is a Efforts to prevent postpartum hemorrhage can be done since the third stage of labor day up to ten with a massage that stimulates the release of oxytocin, causing the process of involution. Information about oxytocin massage is very important to convey to the general public in order to increase knowledge so as to reduce the incidence of bleeding. Methods in community service activities consists of input, process and output. Input in this activity is the mother - PKK cadres, pregnant women in Sub Meteseh. The process is in the form of health education with lectures and demonstrations while the output is the measure of understanding about the prevention of maternal postpartum hemorrhage with pre and post questionnaires given during the event. Perceived outcome of this activity is that participants understand the massage action of oxytocin to prevent postpartum hemorrhage resulting in a change of behavior to take steps to prevent postpartum hemorrhage in the mother. It can be seen from the results of the posttest as much as 40% of participants had a value of 80-60, 60% obtain grades 50-20 while in the posttest as much as 80% of the participants has a value of 90-80, 20% scored 70-60.